P136 Do structured exercise classes for inpatients with COPD increase community pulmonary rehabilitation (PR) referral and completion rates?. (12th November 2015) - Avent, TC; Colclough, RC; Edgar, RG; Owen, C; Swindells, KH; Gompertz, S
Abstract : Introduction: NICE recommends community PR as an essential component of chronic obstructive pulmonary disease (COPD) management, 1 although nationally mean uptake is only 15%. 2 PR has been proven to improve quality of life and to be cost effective. 1 Our team routinely assess and refer COPD inpatients to PR, however, many decline referral. We piloted an inpatient exercise class with the objective of increasing referrals to PR and explored the reasons patients declined referral. Methods: Patients admitted with an acute exacerbation of COPD (June–November 2014) were given the opportunity to attend a Physiotherapy-led exercise class twice weekly. Baseline referral and completion rates to PR were calculated over two separate months during 2013–2014 and comparisons made with rates for the class attendees. Results: Baseline referral rate to PR was calculated at 25%. 50 patients were offered in-patient exercise during the study; 30 agreed (60%). PR referral rate for patients who attended the in-patient class was 57% compared with 40% of those who did not. Baseline PR completion rate was 15%. In those exposed to in-patient exercise, completion rose to 18%. In the group declining inpatient exercise only 13% completed PR. The reasons for declining subsequent referral to PR are outlined in Figure 1 . Discussion: Whilst not achieving statistical significance the referral rate to PR was higher amongst patients exposed to an inpatient exercise class, suggesting an effect on the initial uptake to PR may be improved with this intervention. Completion rates of PR were similar but sample size was insufficient to reliably detect this and it is acknowledged this was a small preliminary study. As an improvement in referral rate to PR was observed the feasibility of providing a routine exercise class warrants further investigation in a larger cohort. Further investigation is also required into why many patients decline PR referral and find it difficult to express reasons why. References: 1 NICE. CG101 Chronic Obstructive Pulmonary Disease-(Update), 2010 2 Stone RA, et al . COPD: Who cares matters . National COPD audit programme: Clinical audit of COPD exacerbations admitted acute units in England and Wales 2014. National clinical audit report . London: RCP, 2015